Phosphate response curves of mycorrhizal Hevea brasiliensis in two sterilised soils - Ikram A; Napi D; Sudin M N (Journal of Natural Rubber Research, 1996)
Monoclonal Hevea brasiliensis GT 1 seedlings were grown with or without introduced arbuscular mycorrhizal fungi in steam-sterilised Segamant and rasau series soils that had been fertilised with Christmas Island phosphate rock and a soluble P source (KH2 PO4) at a wide range of applied phpsphate levels. After 20 weeks, inoculated plants significantly outyielded uninoculated plants in shoot and root growth despite infection of uninoculated plants by indigenous mycorrhizal fungi. The effectiveness of the phosphorus sources applied on shoot and root yields were not significant but affects mycorrhizal development and phosphorus contents in shoots. Plant growth was poor in steamed Segamat series soil due to release of biologically toxic nutrients, even at the higher rates of P applied. Under the conditions of the experiment, the main effect of P rates was significant only in Rasau series soil where increased shoot dry matter was obtained when plants were given the insoluble P source at 200 and 400 mg/kg or KH2 PO4 at 200 mg/kg, than when P was not supplied.
Keywords: Hevea brasiliensis; Mycorrhizal fungi; Phpsphate response